Clinical education in physical therapy : the evolution from student to clinical instructor and beyond - Debra Feingold Stern (Burlington, MA : ones & Bartlett Learning, 2020)
"Clinical Education in Physical Therapy: The Evolution from Student to Clinical Instructor and Beyond serves as a Clinical Education resource for entry-level Physical Therapy students, while serving as an excellent resource for community Clinical Instructors. This new text presents an overview on the rewards and challenges of becoming a Clinical Instructor, the legal issues involved for the academic institution and the clinical sites, clinical education models, student characteristics, establishing a clinical education program, and much more! Each new print copy includes Navigate 2 Advantage Access that unlocks a comprehensive and interactive eBook, online video segments, student practice activities and assessments, a full suite of instructor resources, and learning analytics reporting tools. Navigate 2 is nearly here. In the meantime, we invite you to redeem your Access Code and join our Lounge. Once your Navigate 2 Advantage Access is live, we will notify you via email. With Navigate 2, technology and content combine to expand the reach of your classroom. Whether you teach an online, hybrid, or traditional classroom-based course, Navigate 2 delivers unbeatable value. Experience Navigate 2 today at www.jblnavigate.com/2 "-- Provided by publisher
Keywords: MEDICAL Allied Health Services Physical Therapy; Physical therapy Study and teaching; Physical Therapy Modalities education